Pengembangan Three Degree of Freedom Hexapod sebagai Robot Pemadam Api dengan Sensor UVTron Hamamatsu - Sutawati, Luh Ayu; Kumara, I. N. S; Widiadha, W (Majalah Ilmiah Teknologi Elektro, 2018)
The objective of this project is to design and develop an hexapod robot that can locate fire and extinguish it. The design of the robot consists of mechanical or frame, electronics, and software designs. The hexapod robot is a robot with six legs. The legs are driven by servo motors with Three Degree of Freedom (3DOF) to smooth the movement. The servo control uses Torobot 32 Channel servo controller. The fire detection and estinguishing capability are designed using ultrasonic and infrared sensors together with Uvtron sensor. The fire detection system uses Uvtron Hamamats which detects the presence of ultraviolet light through the sensor tube with detection distance up to five meters. The main controller of the robot is Arduino Mega 2560 microcontroller. The algorithm of the robot movement uses wall-following technique to trace the space hence safe path for the robot to move. The robot will move through the room until it locates a fire and then activate the pump to extinguish it, and performs a fire check again. The performance of the robot is tested following typical room simulation as described in the guidelines of Indonesian Robotic Contest.